2020
DOI: 10.1177/0971333620906758
|View full text |Cite
|
Sign up to set email alerts
|

Śraddhā: Construct Definition from the Bhagavad-Gītā

Abstract: In this article, the construct of śraddhā which is derived from a sacred Hindu text, the Bhagavad-Gītā is explicated. The analysis of text resulted in nine themes, and many behavioural outcomes of śraddhā such as not finding faults in others. Jñāna or knowledge is seen as mediating between śraddhā and mokṣa or liberation. This relationship is moderated by tatparaḥ (or eager engagement in the spiritual practice one has chosen) and saṃyatendriyaḥ (or practicing self-restraint). Śraddhā is considered as one of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…The Indians have the concepts of yama and niyama (see Bhawuk, 2019b for elaboration) which are the foundation for all paths of practice. Bhawuk (2020) showed that 14 of the 26 virtues called daivika sampadas fall in the category of tapas. 7 The overlap of these 14 daivika sampadas with tapas indicates that tapas is a fundamental daivika sampada.…”
Section: Self-cultivationmentioning
confidence: 99%
“…The Indians have the concepts of yama and niyama (see Bhawuk, 2019b for elaboration) which are the foundation for all paths of practice. Bhawuk (2020) showed that 14 of the 26 virtues called daivika sampadas fall in the category of tapas. 7 The overlap of these 14 daivika sampadas with tapas indicates that tapas is a fundamental daivika sampada.…”
Section: Self-cultivationmentioning
confidence: 99%
“…There is a need to build a strong base of Indigenous knowledge for global psychology (Marsella, 1998) to prevent othering. Toward this end, I have employed different methods (e.g., historical analysis, case analysis, auto-ethnography, lexical analysis, literary analysis, bridging life-world and scientific world, building models from scriptures; see Bhawuk, 2020, for references) to identify and develop Indigenous constructs like manas, buddhi, ahaGkAra, Atman, cit or consciousness, lokasaGgraha, adhyAtma or spirituality, lajjA (Bhawuk, 2017), prem or love, and zraddhA (Bhawuk, 2020). I have also developed models of self, models of personal harmony, and a spirituality-based theory of creativity (Bhawuk, 2011).…”
Section: Developing Indigenous Psychological Constructs and Modelsmentioning
confidence: 99%
“…When an Indigenous psychologist does research on Indigenous constructs and models, the from and for is integrated with the about, resolving an issue raised by Held (2020). For example, when I presented the construct of zraddhA from the bhagavadgItA (Bhawuk, 2020), the construct is not only about Indians but also from India and for Indians. To erase the effect of colonization on Indigenous cultural knowledge systems, it is critical for Indigenous psychologists to study constructs from their own cultures.…”
Section: Developing Indigenous Psychological Constructs and Modelsmentioning
confidence: 99%